2014
DOI: 10.6000/1929-4247.2014.03.03.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Calcium, Serum Iron and Nutritional Status among Under-Five Children in Six Municipalities of Abidjan District, Côte d’Ivoire

Abstract: Malnutrition occurs in various forms in the world, especially in African countries. It affects two-thirds of the children in sub-Saharan Africa. In addition to the protein-energy malnutrition (PEM), micronutrient deficiencies also affect many children. The aim of this study was to evaluate the nutritional status, serum iron and serum calcium among underfive children. This study was conducted on a cohort from 480 children in six municipalities of Abidjan: Abobo, Cocody, Koumassi, Marcory, Treichville and Yopoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…This prevalence of chronic malnutrition was identical to that obtained in urban areas in Northern Côte d'Ivoire (17%) [24]. This result was similar to those reported by Koné et al [25] that showed that stunting was the most important prevalence among children from six municipalities of Abidjan district.…”
Section: Discussionsupporting
confidence: 90%
“…This prevalence of chronic malnutrition was identical to that obtained in urban areas in Northern Côte d'Ivoire (17%) [24]. This result was similar to those reported by Koné et al [25] that showed that stunting was the most important prevalence among children from six municipalities of Abidjan district.…”
Section: Discussionsupporting
confidence: 90%